Highly active and stable synergistic Ir–IrO2 electro-catalyst for oxygen evolution reaction. Issue 7 (3rd July 2018) - Zhou, Zhen-Hua; Sun, Wei; Zaman, Waqas Qamar; Cao, Li-Mei; Yang, Ji
ABSTRACT: The design of efficient and stable electrocatalysts is still crucial to realize oxygen evolution reaction (OER) in acid and corrosive environment. Inspired by the metal/metal oxides catalysts, we hydrothermally synthesized Ir–IrO2 composites duly confirmed by X-ray diffraction, X-ray photoelectron spectroscopy, energy dispersive spectrometer (EDS), X-ray absorption data, and transmission electron microscope results. A low onset over-potential of merely 234 mV and a Tafel slope of 53 mV dec −1 were obtained for the prepared catalyst Ir–IrO2 _0.5AF. In addition, Ir–IrO2 _0.5AF catalyst retained high activity for long time under constant potential polarization. The enhanced performance is attributed to the introduction of lower valence Ir as hydrogen acceptor: hydrogen transfers from –OOH intermediate in OER to adjacent H acceptor site, forming intermediate with relatively lower Gibbs free energy, and resulting in higher activity. The present study emphasizes on important role of the lower valence composition in launching H acceptors and providing wide opportunities toward rational designing of efficient and stable electro-catalysts.